Genetic diversity of four broodstocks of tilapia (Oreochromis sp.) from Antioquia, Colombia - Montoya-López, Andrés F.; Tarazona Morales, Ariel M.; Olivera-Angel, Martha; Betancur-López, John J. (Revista Colombiana de Ciencias Pecuarias, 2019)
Background: Tilapia is the most farmed fish in Colombia. However, the genetic diversity and structure of broodstocks in the hatcheries of Antioquia province remains unknown. Objective: To analyze the genetic diversity and structure of one Nile and three red tilapia broodstocks in Antioquia, Colombia. Methods: Fish were genotyped using 24 microsatellite markers of 13 linkage groups in five multiple reactions. Genetic diversity metrics were estimated and null alleles were detected. Analysis of Molecular Variance and analysis of number of clusters were used to describe the relationship between broodstocks. Results: Two microsatellites could not be amplified, and 22 were polymorphic. Average number of alleles per locus ranged 5.77 to 7.91. Locus UNH211 had the most alleles (17), whereas OMO032 had the fewest (4). Except for GM234 and OMO032, the analyzed loci had at least one private allele per population. Average effective number of alleles (3.37–4.03) was always less than the number of observed alleles. Significant deviations from Hardy-Weinberg equilibrium with heterozygote deficiencies were registered. Nine markers showed evidence of null alleles. The expected heterozygosity (0.65 to 0.67 per broodstock) was significantly higher than the observed heterozygosity (0.601 to 0.649) in the four populations. The fixation index for all broodstocks (excluding null alleles) was 0.0766 (95% confidence interval, 0.05092 to 0.10289). According to the molecular variance analysis, the greatest variation was between individuals rather than between groups of broodstocks or individuals within broodstocks. The genetic distance between the Nile and red broodstocks ranged from 0.43 to 0.54. Conclusions: Overall, these findings provide baseline information about the genetic diversity and structure of tilapia broodstocks in Antioquia, Colombia, useful for the management of hatcheries.